2008
DOI: 10.1080/10641260701678181
|View full text |Cite
|
Sign up to set email alerts
|

Predators Are Attracted to Acclimation Cages Used for Winter Flounder Stock Enhancement

Abstract: Acclimation cages are used for juvenile, cultured winter flounder Pseudopleuronectes americanus so that the fish can adjust to their new environment, hone their burial skills, begin pigment change, and recover from the stress of transport to the release site, all in the absence of predation. However, there have been indications that the cages attract the predatory green crab, Carcinus maenas. Studies conducted at the release site in the Hampton-Seabrook Estuary, New Hampshire, USA, determined that green crab a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Key release parameters that affect survival of hatchery fish released into the wild include fish size-at-release (e.g., Hager and Noble, 1976;Tsukamoto et al, 1989;Svåsand and Kristiansen, 1990b;Leber et al, , 1997Leber et al, , 1998Leber et al, , 2005Lorenzen, 2000), release season (e.g., Bilton et al, 1982;Leber et al, 1997Leber et al, , 1998Hines et al, 2008), release habitat and microhabitat (e.g., Leber et al, 1998;Gardner and Van Putten, 2008;Hines et al, 2008), release magnitude (Brennan et al, 2008;Hines et al, 2008), transport and release associated stress (Sulikowski et al, 2005;Fairchild et al, 2009), and acclimatization at release sites (Brennan et al, 2006;Fairchild et al, 2008;Hervas et al, in press). These and similar experimental studies have shown that choices made about release parameters can result in significantly different mortality rates of released hatchery fish.…”
Section: (8) Use Genetic Resource Management To Maximize Effectivenesmentioning
confidence: 98%
“…Key release parameters that affect survival of hatchery fish released into the wild include fish size-at-release (e.g., Hager and Noble, 1976;Tsukamoto et al, 1989;Svåsand and Kristiansen, 1990b;Leber et al, , 1997Leber et al, , 1998Leber et al, , 2005Lorenzen, 2000), release season (e.g., Bilton et al, 1982;Leber et al, 1997Leber et al, , 1998Hines et al, 2008), release habitat and microhabitat (e.g., Leber et al, 1998;Gardner and Van Putten, 2008;Hines et al, 2008), release magnitude (Brennan et al, 2008;Hines et al, 2008), transport and release associated stress (Sulikowski et al, 2005;Fairchild et al, 2009), and acclimatization at release sites (Brennan et al, 2006;Fairchild et al, 2008;Hervas et al, in press). These and similar experimental studies have shown that choices made about release parameters can result in significantly different mortality rates of released hatchery fish.…”
Section: (8) Use Genetic Resource Management To Maximize Effectivenesmentioning
confidence: 98%
“…Recent studies have demonstrated that conditioning or learning of reared fish before release could improve behavioral skills such as feeding, burying and predator avoidance (Hossain et al 2002, Fairchild & Howell 2004, Arai et al 2007, resulting in higher survival of juveniles just after release . However, some negative impacts of conditioning processes have been observed, such as attraction of predators during on-site acclimation using cages (Fairchild et al 2008). Although conditioning prior to release may improve the slightly delayed feeding of spotted halibut juveniles just after release, the fact that juveniles could adapt to the release habitat within 1 wk after release, and subsequently undergo a high incidence of recruitment to the fishery, might indicate that conditioning before release may not be necessary under near-optimal biotic/abiotic release conditions.…”
Section: Adaptation Processes Of Juvenilesmentioning
confidence: 99%
“…However, the cages also can be detrimental by attracting predators to the release site. In a recent study, Fairchild, Rennels and Howell (2008) compared green crab density when cages were absent, present but empty and present and containing flounder. They found that crab density increased dramatically from 1.8 to 4.1 crabs 50 m −2 when empty cages were deployed.…”
mentioning
confidence: 99%
“…Site A is a well‐studied location in the Hampton River that has been used as a release site for previous winter flounder stock enhancement studies. Site B is approximately 250 m downriver from Site A and has been examined as an alternate release site (Fairchild, Rennels et al 2008). Both sites are sandy areas devoid of any macroalgae or structure, about 4 m deep at mean high water, have high salinity and dissolved oxygen, and naturally occurring wild juvenile winter flounder populations (Fairchild, Sulikowski, Rennels, Howell & Gurshin 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation